Impact of Mn2+-Si4+ co-substitution on the electronic structure of Zn0.3Mn0.7Fe2O4 ferrites studied by X-ray photoelectron spectroscopy. Issue 21 (1st November 2022) - Jani, Komal K.; Raval, Pooja Y.; Vasoya, Nimish H.; Nehra, Monika; Singh, Mamraj; Jakhar, Narendra; Kumar, Sandeep; Modi, Kunal B.; Lim, Dong-Kwon; Singhal, Rishi Kumar
Abstract: X-ray photoelectron spectroscopy (XPS) has been employed to explore the electronic structure of Zn0.3 Mn0.7 +x Si x Fe2 - 2 x O4 ( x = 0.0–0.3) ferrite series. The Si2 p XPS spectra insinuated the presence of Si ions in the +4 valence state. The elemental Si 0 and suboxide SiOx are present in the system, the former showing an increase and the latter a decrease in atomic percentage upon Mn–Si substitution. It is also inferred that a fraction of Si 0 might be residing at the grain boundaries; however, more studies are required to substantiate this. The Fe2 p XPS spectra stipulate that ferrous and ferric ions co-occur in the system. The ferrous ions occupy the octahedral sites while the ferric ions dwell on both the octahedral and the tetrahedral sites. The O1 s spectra indicate a remarkable increase in the oxygen defects with increasing Mn–Si substitution ( x ). The Mn2 p XPS data indicate that the Mn +2 states show an overall increasing tendency with increasing Mn–Si concentration. Also, the Mn +4 /Mn +3 ratio shows an increment with an increase in Mn–Si substitution.